Основні напрями підвищення якості вищої освіти в сучасних умовах - Тугай, А. М.; Гойко, А. Ф.; Єлішевич, М. А. (Ways to Improve Construction Efficiency, 2013)
Highlights of improving the quality of higher education to the level of current and future requirements based on a systematic approach, taking into account the main factors affecting the process.